Skin infection by Mycobacterium marinum - diagnostic and therapeutic challenge - Angélica Seidel; Daniel Holthausen Nunes; Camilo Fernandes; Gabriella Di Giunta Funchal (Sociedade Brasileira de Dermatologia, 2022)
Abstract The number of skin infections caused by atypical mycobacteria has increased in recent decades. They usually appear after contact with wounds and interruptions in the integrity of the skin. The present report describes a case of cutaneous infection by Mycobacterium marinum, in a young, immunocompetent patient, with a prolonged evolution, diagnosed through a skin lesion culture (from a spindle biopsy of the skin). The patient was treated with multidrug therapy, including clarithromycin, doxycycline, and rifampicin, due to the lesion extent, with satisfactory results. A brief review of the literature is also provided.